Analysis of the effect of Inflation on Purchasing Power in Indonesia - Aisyah, Siti; Daud, Anshar; Mulyanti, Dwi Retno; Dewi, Grace Citra; Harmadi, Ashur (Pt. Anagata Sembagi Education, 2025)
This study examines the impact of inflation on purchasing power in Indonesia, analyzing how fluctuations in inflation influence the ability of individuals to meet their basic needs. Utilizing a quantitative research design, the study focuses on the years 2013-2023 and employs various statistical methods, including regression analysis and ANOVA, to explore the relationship between inflation, purchasing power, and economic well-being. The results indicate a significant negative correlation between inflation and purchasing power, with inflation explaining approximately 65% of the variance in purchasing power. The findings highlight that inflation has a pronounced effect on lower-income groups, exacerbating their financial challenges. Moreover, the study contributes to the literature by providing empirical evidence on the effects of inflation on purchasing power in Indonesia, offering valuable insights for policymakers. The research emphasizes the importance of controlling inflation to maintain economic stability and enhance the well-being of the population, particularly vulnerable groups.